Rearrange:

Rearrange the equation by individually what is to the ideal of the equal authorize from both political parties of the equation : 3-2*(9+2*m)-(m)=0

Step by action solution :

Step 1 :

Equation in ~ the end of action 1 :

(3 - 2 • (2m + 9)) - m = 0

Step 2 :

Step 3 :

Pulling out prefer terms :3.1 pull out prefer factors:-5m - 15=-5•(m + 3)

Equation in ~ the end of action 3 :

-5 • (m + 3) = 0

Step 4 :

Equations i beg your pardon are never ever true:4.1Solve:-5=0This equation has actually no solution. A a non-zero consistent never equates to zero.

Solving a solitary Variable Equation:

4.2Solve:m+3 = 0Subtract 3 native both sides of the equation:m = -3

One systems was discovered :

m = -3




You are watching: 3−2(9+2m)=m

Why discover this

*

Terms and topics

*

Related links

*

abc
a
x
y
/
|abs|
( )
7
8
9
*
4
5
6
-
%
1
2
3
+
0
,
.
=
abc
a
b
c
d
e
f
g
h
i
j
k
l
m
n
o
p
q
r
s
t
u
v
w
x
y
z

.
*



See more: Does Aquarius Male After Breakup Think Of His Woman, Dealing With An Aquarius Man Break

earlier to top